An exploration of organized crime in Italian ports from an institutional perspective. Presence and activities - Antonelli, Marco (Trends in organized crime, 2021)
The article will present the results of a qualitative research into organized crime in the Italian port system. It is a pioneering attempt to assess an extensive and diachronic perspective on the presence and activities of organized crime groups into the Italian seaports in order to provide a systematic analytical map through the analysis of institutional law enforcement reports. The article attempts to shed light on an overlooked topic, analytically relevant insofar as it examines OCGs’s activities in a specific and particular space representing an opportunity to obtain profits and social connections. Moreover, it analyses OCGs tendency to be involved in legal and illegal businesses, their ability to persist in space and time, and their skills in moving abroad., The results show that organized crime activities are permanent and largely widespread in the main harbours all over the country, particularly in Ancona, Cagliari, Genova and Gioia Tauro; organized crime groups operate mostly in illegal business and in particular in illicit trafficking of drugs, cigarettes and counterfeit goods; the Italian mafia ‘ndrangheta seems to be able to persist in space and time within several seaports. The study shows that simultaneous processes of specialization in illegal markets and diversification in seaports are ongoing.